2022
DOI: 10.5334/jime.749
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation of Learning and the Co-Design of Personalized Learning Pathways in Higher Education: A Theoretical Model Approach

Abstract: The way we learn is changing, and this requires seeking learner-centred pedagogical strategies. Based on this idea, this paper is about the process of construction and validation of a pedagogical model approach based on the perspectives of co-design, learning pathways and self-regulated learning. Through a process of Design Based Research, different techniques and instruments have been applied to collect information aimed at the creation and validation of a co-design model in the construction of personal learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Figure 7 shows implemnettaion of perspective model of formation of communicative competency of document managers in the system of continuing education. • improvement of language skills like listening, speaking, reading and writing (Yoel et al, 2022); • increasing of self-learning skills (Lemmetty & Collin, 2020;Santoso et al, 2022); • formation of problem solving and conflict management skills (Mantra et al, 2019); • buildings of digital competency and ability to use ICT propertly while performing professional activities (Akorede & Adeniyi, 2020;Poplavskyi & Bondar, 2021); • integration of different communicative experiences (Shibli-Rahhal et al, 2019); • contribution to career development (Mammadova, 2021;Oriji & Uzoagu, 2019); • development of activity-specific skills and soft skills (Anosova et al, 2022); • formation of ability to work independently (Lemmetty & Collin, 2020;Santoso et al, 2022;Villatoro & de-Benito, 2022); (Holford et al, 2022); • increasing of motivation to operate in communicative environment (Ismail & Jarrah, (2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 shows implemnettaion of perspective model of formation of communicative competency of document managers in the system of continuing education. • improvement of language skills like listening, speaking, reading and writing (Yoel et al, 2022); • increasing of self-learning skills (Lemmetty & Collin, 2020;Santoso et al, 2022); • formation of problem solving and conflict management skills (Mantra et al, 2019); • buildings of digital competency and ability to use ICT propertly while performing professional activities (Akorede & Adeniyi, 2020;Poplavskyi & Bondar, 2021); • integration of different communicative experiences (Shibli-Rahhal et al, 2019); • contribution to career development (Mammadova, 2021;Oriji & Uzoagu, 2019); • development of activity-specific skills and soft skills (Anosova et al, 2022); • formation of ability to work independently (Lemmetty & Collin, 2020;Santoso et al, 2022;Villatoro & de-Benito, 2022); (Holford et al, 2022); • increasing of motivation to operate in communicative environment (Ismail & Jarrah, (2019).…”
Section: Discussionmentioning
confidence: 99%
“…tailoring the educational materials to learners' needs (Yoel et al, 2022); transformation of the teaching experience and students' learning experience to achieve educational goals (Shemshack & Spector, 2020) Instructional video (Schmid et al, 2022) Interactive testing (Bekmanova et al, 2021) Work with multimedia textbook (Bekmanova et al, 2021) Didactic cards (Villatoro & de-Benito, 2022) Work with documents (Bekmanova et al, 2021) Quiz and games (Shemshack & Spector, 2020;Villatoro & de-Benito, 2022) Storytelling (Shemshack & Spector, 2020) Concept test (Shemshack & Spector, 2020;Villatoro & de-Benito, 2022) Peer learning students' learning with and from each other (Johler, 2022); horizontal educational process when students participate in instruction and evaluation (Johnson et al, 2021) Warm-up activity (Duran et al, 2019) Collaborative work (Mantra et al, 2019) Reporting (Johler, 2022) Conference (Johler, 2022;Johnson et al, 2021) Preparation of information messages (Johnson et al, 2021) Picture description (San Martin et al, 2020) Parallel control (Mantra et al, 2019) Webinar (Yang & Kim, 2022) Independent practice (Mitsiou, 2019) Peer evaluation (Johler, 2022;Johnson et al, 2021) Self-regulated learning Involvement of students' into organization and control of the learning environment (Lemmetty & Collin, 2020); process when students actively manage their own learning experiences (Mejeh & Held, 2022); process when learners monitor and control their cognition, motivation, and ...…”
Section: Group Workmentioning
confidence: 99%
“…Participatory co-design begins with cooperation among educational participants, progresses via discussion and agreement, and culminates in co-creation (Bovill, 2020). Various levels of engagement are formed within co-design because there are varying interactions between participants (between educators, between learning peers, between learner and educator, or between professionals) and varying levels of participation (Villatoro Moral & de-Benito Crosetti 2022). Recent research has revealed substantial benefits of co-design: it can enhance deeper learning among students and further give educators critical insights to plan curriculum and instruction more effectively (Gros, 2019).…”
Section: Co-design In Collaborative Learningmentioning
confidence: 99%